Collaborative Online International Learning to Address Mental Health Across Cultures with an Islamic Perspective - Gunawan, Teddy Surya; Kartiwi, Mira; Lubis, Asmuliadi; Arifin, Muhamad (IAES Indonesian Section, 2024)
This study examines the impact of a Collaborative Online International Learning (COIL) project on enhancing students’ cross-cultural understanding, collaborative skills, and problem-solving abilities in addressing mental health issues through technology, enriched by insights from an Islamic perspective. The project connected students from the International Islamic University Malaysia’s (IIUM) Operating Systems course and Shenandoah University’s Occupational Therapy in Mental Health Practice course, fostering a dynamic, interdisciplinary learning environment. Students worked in diverse teams, engaging in activities such as video introductions, infographic creation, and presentations on technological applications in mental health, facilitated by platforms like Zoom, Google Sites, and WhatsApp. Evaluations, including Programme Outcome (PO) analyses, revealed that over 80% of students achieved “Acceptable” or higher levels in applying engineering knowledge (PO1) and problem analysis (PO2), reflecting the success of the project in meeting its learning objectives. Student reflections captured on Flipgrid further underscored the project’s impact, with participants highlighting improved cultural sensitivity, adaptability to a global professional context, and collaborative problem-solving despite challenges such as time zone differences. The inclusion of Islamic perspectives provided a holistic lens, emphasizing spiritual and technological solutions to mental health issues through values such as patience (sabr), gratitude (shukr), and trust in Allah (tawakkul). This study underscores COIL’s potential as a transformative pedagogical approach for preparing students to navigate multicultural, technology-driven environments while fostering global mental health awareness. It offers actionable insights for educators and policymakers seeking to integrate cultural and religious perspectives into interdisciplinary education